A chromatographic method for the determination of sucrose in commercial beverages with added sugar - Pérez López, Esteban (2023)
Derived from the excessive consumption of sugar in Costa Rican society and the problems derived largely from the consumption of commercial beverages with high sucrose content, and its consequent effect on public health. This article shows the development and validation of an analytical methodology free of interference by high-performance liquid chromatography coupled to a refractive index detector (HPLC-IR), for the quantification of sucrose in commercial beverages with added sugar. The most suitable chromatographic conditions for the quantification of sucrose were determined in the Chemical Laboratory of the Greece Campus of the University of Costa Rica; where the use of a Phenyl chromatographic column of 250 x 4.6 mm x 5 µm particle stands out, using ultrapure water as the mobile phase. In addition, the validation of the analytical performance parameters: linearity, repeatability, intermediate precision, truthfulness, specificity, which fully complied with the standards provided for each analytical parameter evaluated. In this way, a new method is established and validated to quantify sucrose in commercial beverages with added sugar, ensuring efficiency and effectiveness in quantification under validated conditions.